Simultaneous and sensitive detection of Mycobacterium tuberculosis and SARS-CoV-2 antigens employing an electrochemical impedance spectroscopy aptasensor - Zhumabekova, Zhazira; Elebessov, Timur; Pham, Tri Thanh; Kanayeva, Damira (Frontiers in Bioengineering and Biotechnology, 2025)
MPT64 and S-glycoprotein are essential biomarkers for detecting tuberculosis and coronavirus, two prevalent infectious diseases worldwide. In this study, we developed an electrochemical impedance spectroscopy (EIS)-based aptasensor fabricated to detect both target antigens simultaneously, employing a dual-platform approach on a screen-printed gold electrode (SPGE). Thiolated aptamers targeting both antigens were functionalized on the surface of the SPGE, which was then blocked with 6-mercapto-1-hexanol and assessed for the detection of target biomarkers after a 10-min incubation period. The performance was evaluated using EIS, which can detect target antigens in the range of 0.01 pg/mL to 10 pg/mL in both buffer and human serum, quantified through charge transfer resistance (Rct) values. For MPT64 and S-glycoprotein in buffer, the optimized aptasensor achieved detection limits of 0.053 pg/mL and 0.319 pg/mL, respectively. In human serum, the detection limit for MPT64 was 0.085 pg/mL, whereas it was 1.421 pg/mL for S-glycoprotein. The surface functionalization of the SPGE was confirmed through cyclic voltammetry, contact angle measurements, and atomic force microscopy. The aptasensor maintained good storage stability for up to 22 days. This label-free EIS-based aptasensor is a sensitive, selective, and reproducible platform for simultaneously detecting tuberculosis and SARS-CoV-2 biomarkers, demonstrating promising potential for clinical applications.